Mendobrak Sekat Pembatas: Suatu Kajian Etika Poskolonial Sebagai Upaya Merobohkan Diskriminasi terhadap Homoseksual - Purba, Fredi Ardo (STFT Jakarta, Indonesia, 2024)
Homosexuality is still an issue that has its pros and cons. Very few churches in Indonesia are open to those with homosexual orientation. Churches tend to reject and discriminate against homosexuals as actions that are against the Bible and against God’s will. This is due to the view of heteronormativity, which is the view that heterosexuality is the truth and must be owned. Heteronormativity is a colony culture that is still inherent today. It creates hegemony and domination between heteronormativity (colonizer) and homosexuality (colonized). However, how should the church respond to homosexuality in postcolonial discourse? The research was conducted using the literature study method by reviewing Homi K. Bhabha’s liminality theory. The research was conducted with the aim of being a postcolonial effort in providing space between the colonizer (heteronormativity) and the colonized (homosexuality) to conduct cultural negotiations. The results showed that Postcolonial ethics with the perspective of Bhabha’s liminality theory formed a relationship of cultural exchange by heteronormativity with homosexuality, creating an attitude of acceptance. This has an impact on the church's attitude that is inclusive of homosexuality and does not discriminate. The church should view homosexuality as a reality of gender diversity.